Sediment Release in the Benguela Upwelling System Dominates Trace Metal Input to the Shelf and Eastern South Atlantic Ocean - Liu, Te; Krisch, Stephan; Xie, Ruifang C.; Hopwood, Mark J.; Dengler, Marcus; Achterberg, Eric P.; Krisch, Stephan; 1 GEOMAR Helmholtz Centre for Ocean Research Kiel Kiel Germany; Hopwood, Mark J.; 1 GEOMAR Helmholtz Centre for Ocean Research Kiel Kiel Germany; Dengler, Marcus; 1 GEOMAR Helmholtz Centre for Ocean Research Kiel Kiel Germany; Achterberg, Eric P.; 1 GEOMAR Helmholtz Centre for Ocean Research Kiel Kiel Germany (Global Biogeochemical Cycles, 2022)
Upwelling of subsurface waters injects macronutrients (fixed N, P, and Si) and micronutrient trace metals (TMs) into surface waters supporting elevated primary production in Eastern Boundary Upwelling Regions. The eastern South Atlantic features a highly productive shelf sea transitioning to a low productivity N‐Fe (co)limited open ocean. Whilst a gradient in most TM concentrations is expected in any off‐shelf transect, the factors controlling the magnitude of cross‐shelf TM fluxes are poorly constrained. Here, we present dissolved TM concentrations of Fe, Co, Mn, Cd, Ni, and Cu within the Benguela Upwelling System from the coastal section of the GEOTRACES GA08 cruise. Elevated dissolved Fe, Co, Mn, Cd, Ni, Cu and macronutrient concentrations were observed near shelf sediments. Benthic sources supplied 2.22 ± 0.99 μmol Fe m−2 day−1, 0.05 ± 0.03 μmol Co m−2 day−1, 0.28 ± 0.11 μmol Mn m−2 day−1 and were found to be the dominant source to shallow shelf waters compared to atmospheric depositions. Similarly, off‐shelf transfer was a more important source of TMs to the eastern South Atlantic Ocean compared to atmospheric deposition. Assessment of surface (shelf, upper 200 m) and subsurface (shelf edge, 200–500 m) fluxes of Fe and Co indicated TM fluxes from subsurface were 2–5 times larger than those from surface into the eastern South Atlantic Ocean. Under future conditions of increasing ocean deoxygenation, these fluxes may increase further, potentially contributing to a shift toward more extensive regional limitation of primary production by fixed N availability. Key Points: Shelf sediments release redox‐sensitive trace metals (TMs) to overlying oxygen‐depleted waters in the Benguela Upwelling System. Sediment‐derived TMs are upwelled and laterally transported constituting a major source to shelf waters and to the eastern South Atlantic. Subsurface fluxes of dissolved Fe and Co from the shelf edge play an important role in supplying Fe and Co to the eastern South Atlantic. China Scholarship Council, CSC ...